Woman pullers: pimping and sex trafficking in a Mexican Border City - Zhang, Sheldon (Crime, law and social change, 2011)
Much has been written about sex trafficking in the past decade, although empirical studies have remained few. Even less research has been done on those who make a living by facilitating the movement of women and children in the sex industry. This paper is based on a three-year study in Tijuana, Mexico, in which 92 sex trade facilitators were interviewed. Findings suggest a far more complex social process than portrayed by the anti-trafficking literature. Men and women of diverse backgrounds developed niches in Tijuana’s sex industry, by bringing women into contact with customers. This business appeared to be dominated by Mexican entrepreneurs, with no evidence of any systematic collaborations with either local criminal organizations or foreign traffickers. There appeared to be no shortage of women willing to work in the sex industry, suggesting limited prospect for coerced prostitution. Still, a small number of pimps reported using "persuasion" to recruit women of particular types from interior Mexico. Commissions or referral fees were the most common form of income received by pimps for their services, and the rules on how money was to be made and split between sex workers and venue owners appeared well established. While a few respondents could sustain a livelihood through pimping, the majority held other jobs.